Set up the equation like this: x+x-6=10. You filled in x-6 for y because the second equation says y=x-6. When you solve, you add 6 to both sides of the equation (this is the addition property of equality in geometry). You now have x+x=16. Now, you can combine like terms (this would be the proof combine like terms in geometry) and you would be able to combine like terms because each of those x's are truely 1x+1x because a variable without a coefficient (the number in front of the variable) is an understood 1. So, (1)x+(1)x=2x. So, you have 2x=16. Now, divide by 2 on each side to get that x alone. This is the division property of equality in geometry. You find x=8. You now have the point (8,y) Now to find the y, plug in the 8 for x in one of the equations. If you plug it into the equation x+y=10 you get 8+y=10. Now subtract 8 from both sides (Subtraction property of equality in geometry). y=2. You get the same answer if you plug in 8 for the other equation. y=8-6. 8-6 is 2. Hope this helps! :)